2014
DOI: 10.1080/13603116.2014.930519
|View full text |Cite
|
Sign up to set email alerts
|

Educational reform in Japan towards inclusion: are we training teachers for success?

Abstract: Within a tradition of a dual regular and special education system in Japan, the Government is promoting education reform that encourages an inclusive approach to education. This research investigates whether teachers are being trained for successful inclusion in Japan by reviewing the perceptions of all preservice teachers in one university regarding their readiness for becoming inclusive practitioners. A move towards an inclusive approach to education in Japan is being promoted through collaboration and suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 12 publications
1
32
0
4
Order By: Relevance
“…The high degree of concerns of pre-service teachers noted at both stages of the course was found to be worrisome, with participants being mainly concerned about the lack of resources for inclusive education. This result is not new and is frequently identified as a barrier to implement inclusive education in previous research across both developed and developing countries (Forlin, 2013b;Forlin, Kawai, & Higushi, 2014;Sharma, Forlin, Deppeler, & Guang-xue, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…The high degree of concerns of pre-service teachers noted at both stages of the course was found to be worrisome, with participants being mainly concerned about the lack of resources for inclusive education. This result is not new and is frequently identified as a barrier to implement inclusive education in previous research across both developed and developing countries (Forlin, 2013b;Forlin, Kawai, & Higushi, 2014;Sharma, Forlin, Deppeler, & Guang-xue, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…A possible explanation for this might be that younger teachers have had more opportunities for training on inclusive education in their teacher education programs. It has been suggested that pre-service teachers who had more training on special needs education showed more positive attitudes toward inclusive education (Forlin et al, 2015). Another possible explanation is that teachers' attitudes became more negative through their teaching career because they have had difficulty including children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported that the support system for children with disabilities in regular classes is underdeveloped (e.g., Hamaya, 2006;Hirose & Tojo, 2002). For instance, Ueno and Nakamura 2011 (Forlin et al, 2015). Even though teachers' interest in inclusive education is relatively high and teachers realize that such education is necessary, their knowledge level is low, and they experience considerable anxiety about including children with disabilities in their classrooms (Ueno & Nakamura, 2011).…”
Section: Inclusive Education In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussions in the literature surrounding teacher preparation for inclusion are extensive (e.g., Allday, Neilsen-Gatti, & Hudson, 2013;Killoran, Woronko, & Zaretsky, 2014;McHatton & Parker, 2013). While there is widespread support for university-based teacher preparation, there continues to be national and international concern about the adequacy of that preparation for inclusion, and whether it provides what schools require to address student learning needs (Forlin, Kawai, & Higuchi, 2015;Husebo, 2012;Snyder, 2012). Serious concerns exist about whether pre-service teachers can effectively employ inclusive teaching practices (Forlin, Loreman, Sharma, & Earle, 2009;Jung, 2007;Lombard, Miller, & Hazelkorn, 1998;Reed & Monda-Amaya, 1995).…”
Section: Introductionmentioning
confidence: 99%